SUSTAINABILITY REPORTING SEBAGAI MEDIA PERUSAHAAN DALAM MENGEMBANGKAN DAN MELAPORKAN KEBIJAKAN BISNIS BERKELANJUTAN - Maharani, Satia Nur (Jurnal Ekonomi Modernisasi, 2014)
Suistainability is about long-term value creation not only for company but also for employees, customers, the industry sector, investors and the communities where the company does business. The ability of company to create long-term value is based on its understanding of and response to demands of society and on recognizing that environtmental, social, economical and ethical factors affect the bussines strategy.This article identifies drives for organitation to adopt corporate social responcibility and produce corporate suistainability report.